Multidisciplinary Management of Febrile Neutropenia: Consensus Statement. Lima, Peru - Alcarraz, Cindy (2021)
Background: To provide recommendations based on the best available scientific evidence for the multidisciplinary management of febrile neutropenia. The development included the stages: approval of the creation of the Working Group (WG); CPG search; analysis and synthesis of the evidence that led to establishing the recommendation of the selected CPGs, design of the consensus document, internal review. All phases were carried out through panel meetings using virtual platforms during 03 months. The “GRADE” system was used to establish the strength and direction of the recommendations. The recommendations cover the prevention, diagnosis and treatment of febrile neutropenia in oncohematological patients. Twenty-eight recommendations were developed. The topics approached were: correct evaluation; timely diagnosis, adequate antibiotic treatment, vaccination against influenza and pneumococcus, administration of colony-stimulating factor and special management of pediatric patients for diagnosis, treatment.